The positive effects of positive coping on mental health in college students during the COVID-19 campus lockdown - Li, Meiqi; Chen, Lijun (Frontiers in Public Health, 2023)
Objectives Isolation has been an effective method to control the spread of COVID-19 over the past 3 years. However, lifestyle changes may have a negative impact on mental health. To examine the effects of positive coping on mental health in college students during the COVID-19 campus lockdown, this study conducted an online cross-sectional survey. Methods In October 2022, following a prolonged campus lockdown of nearly 3 years, 313 university students from a university in Shandong Province, China, were invited to complete an online questionnaire. The questionnaire comprised a self-administered general situation questionnaire, the Simple Coping Style Scale, and the Hospital Depression and Anxiety Scale. Results (1) The analysis of variance revealed a significant main effect of coping Style on depression [F(4,300) = 2.446, p = 0.047] during the COVID-19 campus lockdown. A post-hoc test indicated that college students who engaged in study (p = 0.012) or sports (p = 0.027) during their free time had significantly lower depression scores than those who used the Internet. (2) Independent sample t-tests showed significant differences in positive and negative coping styles among college students in terms of depression (t = 6.891, p < 0.001) and anxiety scores (t = 7.745, p < 0.001). (3) Pearson correlation analysis demonstrated a negative correlation between positive coping style and anxiety (r = −0.378, p < 0.001), and between positive coping style and depression (r = 0.427, p < 0.001). Positive correlations were also found between the negative coping style and anxiety (r = 0.155, p = 0.007), and between the negative coping style and depression (r = 0.190, p < 0.001). Discussion The study suggested that fostering positive coping in students can mitigate mental health issues during crises, providing a blueprint for university mental health initiatives during epidemics.